A Soft OR Approach to Fostering Systems Thinking: SODA Maps Plus Joint Analytical Process. (July 2016) - Wang, Shouhong; Wang, Hai
ABSTRACT: Higher order thinking skills are important for managers. Systems thinking is an important type of higher order thinking in business education. This article investigates a soft Operations Research approach to teaching and learning systems thinking. It outlines the integrative use of Strategic Options Development and Analysis maps for visualizing and assessing systems thinking and the joint analytical process for systems thinking development. This approach has been applied in an MBA course, and has demonstrated its usefulness for students in developing systems thinking skills.